2021
DOI: 10.3390/jmse9080895
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing and Maritime Spare Parts: Benefits and Obstacles for the End-Users

Abstract: 3D printing or additive manufacturing (AM) (in the industrial context) is an innovative, as opposed to subtractive, technology, bringing new opportunities and benefits to the spare part supply chain (SPSC). The aim of this work is to capture the views of the stakeholders at the end of the chain, extruding factors that will benefit the end-user and the factors that are likely to be an obstacle, by employing the questionnaire method. Company objectives regarding spares (cost reductions, improvement of services, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Studies that incorporate the two key terms “AM (or 3DP)” and “maritime industry” were focused on exploring the potential of AM technology in supplying spare parts to the maritime industry rather than the future of the world trade network (Jha, 2016; Junghans et al. , 2021; Kostidi and Nikitakos, 2017; Kostidi et al. , 2021; Sanchez-Gonzalez et al.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that incorporate the two key terms “AM (or 3DP)” and “maritime industry” were focused on exploring the potential of AM technology in supplying spare parts to the maritime industry rather than the future of the world trade network (Jha, 2016; Junghans et al. , 2021; Kostidi and Nikitakos, 2017; Kostidi et al. , 2021; Sanchez-Gonzalez et al.…”
Section: Resultsmentioning
confidence: 99%
“…Another study identified the limited effectiveness of 3DP for spare part industries under the conditions of high-demand and multi-item scenarios wherein printing is performed in-house (Arbabian and Wagner, 2020). Other studies explored the potential of 3DP technology in maritime spare part manufacturing (Kostidi and Nikitakos, 2017;Kostidi et al, 2021;Tas ¸and S ¸ener, 2019;Vujovic et al, 2018). Impact on global trade Globalization is the process of integrating national economies into a global economic system (Feenstra, 1998).…”
Section: Impact On Manufacturing Technology and Industrial Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits from this approach can improve operational efficiency in areas of spare parts and tooling. However, there are some technical concerns regarding the static environment that those AM techniques require for quality of deposited or printed material (Strickland [2016], Kostidi et al [2021]).…”
Section: Naval and Offshore Applicationsmentioning
confidence: 99%
“…Benefits and barriers for end users of spare parts printing are discussed in Ref. [ 3 ]. 3D-printing of spare parts is considered in the training of marine engineers [ 4 ].…”
Section: Introductionmentioning
confidence: 99%